The fateful triangle : race, ethnicity, nation - Hall, Stuart, 1932-2014 (Harvard University Press, 2017)
Identities are not something we are born with, Hall argues, but are formed and transformed in the discourses of nation, ethnicity, and race. Casting his glance over the modern age, he shows how the imperial view of civilized-versus-barbarian gave way to a politics of identification that grew ever more unpredictable under late 20th century conditions of globalization. Race was long ago discredited by science yet it persists because it operates as a signifier, making meanings out of the binary representation of difference. From Renaissance to Enlightenment, stability prevailed in a West-centric order that fixed "their difference" against "our modernity," but the multi-accentual slide of signifiers also gave rise to new identities among subordinated subjects as well. Ethnicities that exclude others close down the multiple voicing built into every discourse, whereas Hall shows that "black" took on alternative meaning when Caribbean and South Asian migrants fought racism through alliances based not on genetic or cultural grounds but by opening the signifying chain to recodings. Migration is today at the heart of the contradictory tensions thrown up by global dislocations that have unsettled traditional bonds of collective belonging, although when nations make the rights of citizenship conditional on cultural homogeniety what Hall reveals is the extent to which liberal democracy's universalist values were grounded in an assimilationist worldview that has yet to be fully dismantled.--